Peran Kebudayaan dalam Dunia Pendidikan di Kabupaten Sintang - Tsalitsa, Puja; Purnawan, Endar; Pusarti, Melja; Fatmawati, Ela (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2024)
This journal discusses practical aspects of education that cannot be separated from cultural values. Through the analysis of literature review, this research provides deep insight into the role and interrelated relationship between culture and education, as well as strategies for strengthening education through local cultural values in the world of education in Sintang Regency. The method used in this study is a literature study with a descriptive qualitative approach. The results showed that culture is an integral part of the educational process. The role and relationship between culture and education in Sintang Regency is manifested in the vision of the Sintang Regency Education and Culture Office, which aims to create equitable and quality education services to form an intelligent and cultured society in Sintang Regency. The strategy of strengthening education through local cultural values in Sintang Regency is implemented through various activities, one of which is through the Strengthening the Profile of Pancasila Students in the context of formal education in schools, as a concrete effort to introduce and root local culture and wisdom.